METHODS FOR THE PREVENTION OF SCHEUERMANN’S DISEASE IN CHILDREN WITH HEREDITARY DISORDERS OF THE DEVELOPMENT OF CONNECTIVE TISSUE - Ivanovich , Anton; Leonidovich , Victor; Venyaminova , Elena; Kolokoltsev, Mikhail; Botagariyev, Tulegen; Sarsenbayeva , Svetlana (Revista Inclusiones, 2020)
The research is based on 30 patients with hereditary connective tissue disorders observations over the period 2011 - 2020. This pathological condition is a skeleton systemic disease, based on the vicious development of connective tissue. In the dynamic observation course, the main clinical symptoms of the disease were characterized, among other things, by the presence of curved limbs due to previously suffered fractures (from 3 or more in each patient’s medical history), muscle hypotonia, vicious posture (scoliotic, kyphotic, kyphoscoliotic, flat back), blue scleras’ visualization, the presence of carious teeth. The results of laboratory, x-ray, and densitometric examination methods were the final link in making a clinical diagnosis. Early detection of connective tissue pathology allows avoiding and minimizing the most dangerous complications of the disease, such as idiopathic scoliosis, early juvenile osteochondrosis, Scheuermann’s disease.